1974
DOI: 10.1152/ajplegacy.1974.227.2.396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclic adenosine nucleotides on fluid absorption by different segments of proximal tubule

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1975
1975
2003
2003

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…In studies utilizing the in vitro microperfusion technique, this value has averaged approximately 1.3 nl/ mm per min in tubules from rabbits slightly smaller than those used in the present study (2,4,5). In addition, Hamburger, Lawson, and Dennis have suggested that the proximal convolution is quite heterogeneous (16). Absorptive rates in the early part of the microperfused rabbit proximal tubule were closer to the values obtained in vivo averaging 1.6 nl/mm per min, while in late proximal tubules water movement was approximately 0.5 nl/mm per min, a value quite similar to that found in the straight portion of the proximal tubule.…”
Section: Discussioncontrasting
confidence: 47%
“…In studies utilizing the in vitro microperfusion technique, this value has averaged approximately 1.3 nl/ mm per min in tubules from rabbits slightly smaller than those used in the present study (2,4,5). In addition, Hamburger, Lawson, and Dennis have suggested that the proximal convolution is quite heterogeneous (16). Absorptive rates in the early part of the microperfused rabbit proximal tubule were closer to the values obtained in vivo averaging 1.6 nl/mm per min, while in late proximal tubules water movement was approximately 0.5 nl/mm per min, a value quite similar to that found in the straight portion of the proximal tubule.…”
Section: Discussioncontrasting
confidence: 47%
“…Even if sodium transport were comparable in the convoluted portion of SN and JMN, these two measurable parameters would still seemingly be different if significant sodium transport occurred in the pars recta and (or) descending limb of SN. In studies with the isolated tubular perfusion technique, sodium and water movement in the straight portion of the proximal tubule have been found to be -Y2-1/3 of the values obtained from segments of the convoluted tubules per unit length (19)(20)(21)(22). In further in vitro studies, however, no sodium transport was found to occur along the descending limb of Henle's loop (8).…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, furosemide (5 mg/kg loading and 5/mg/kg per h) given during Ringer loading completely reversed the segmental pattern, 35.5 and 28.8% at late distal tubule and papillary base, respectively, P <0.005. These studies demonstrate that the net addition of sodium Received for publication 3 June 1977 and in revised form 22 March 1978. between late distal tubule and papillary base during Ringer loading is not limited to immature rats and that the segmental pattern does not occur in nonvolume-expanded animals. Further, the reversal of the net addition pattern with furosemide, but not chlorothiazide, and the comparable proximal nephron delivery rates in Ringer loading suggest that the loop of Henle of juxtamedullary nephrons reabsorbs less sodium than the same portion of superficial nephrons in this setting.…”
mentioning
confidence: 80%
“…Consequently, in this respect, intracellular signal transduction is significantly different in the efferent ducts from their homologue, the proximal kidney tubules. In the latter, both cAMP [26][27][28][29][30] and cGMP [31] inhibit fluid reabsorption at about the same concentrations.…”
Section: Discussionmentioning
confidence: 92%
“…It has been established that both cyclic adenosine 3Ј,5Ј-monophosphate (cAMP) and cyclic guanosine 3Ј,5Ј-monophosphate (cGMP) are involved in regulating fluid transport in a number of other tissues. Both stimulate fluid secretion in intestines of humans [21] and rats [22][23][24][25], causing diarrhoea, and both inhibit fluid reabsorption in the proximal tubules of the kidney of a number of vertebrate species [26][27][28][29][30][31]. However, cAMP alone activates fluid secretion in canine pancreatic [32] and gallbladder epithelium [33], equine sweat glands [34], rat submandibular acinar cells [35], frog retinal pigment epithelium [36], and insect salivary glands [37,38], but activates fluid absorption in lung aveolar epithelium [39,40].…”
Section: Introductionmentioning
confidence: 99%